(untitled) (Journal of actual problems of jurisprudence, 2022)
The article is devoted to the legal analysis of Art. 277 of the Criminal Code of the Republic of Kazakhstan on liability for violation of safety rules during mining or construction work. The study showed that the public danger of this act in the presence of a number of unfavorable factors (organizational, legal, technical, etc.), the low effectiveness of the preventive measures taken is steadily increasing. The paper presents the dynamics of this type of violation of labour protection rules over the past five years, the importance, theoretical and practical significance of establishing the type of work carried out and the specific point of the violated safety rules for the correct qualification of the act is noted. Taking into account the doctrine of criminal law and examples from judicial practice, the most characteristic types of violation of safety rules during mining or construction work, signs of the subject of criminal law violation and its difference from other related criminal law violations are indicated. Keywords: violation of safety rules, mining and construction work, criminal liability, legal regulation.